1995
DOI: 10.1159/000184256
|View full text |Cite
|
Sign up to set email alerts
|

Final Height in Children with Growth Hormone Deficiency

Abstract: Forty-six patients (28 boys, 18 girls) were treated with growth hormone (GH) for short stature. Twenty-eight patients had total growth hormone deficiency (GHD), 12 partial GHD and 6 patients had short stature without GHD. Brain tumours were the cause of GHD in 8 patients and multiple pituitary hormone deficiency was present in 9 children. All patients received GH with subcutaneous injections only, 6-7 times/week. Mean final height for all patients was -1.11 SDS and was similar in boys ( 1.09 SDS) and girls (-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 6 publications
3
20
0
3
Order By: Relevance
“…In 34 GHD patients, of whom 6 had isolated GHD and 28 multiple pituitary hormonal deficiencies, treated with 2 or 3 weekly injections of extracted hGH, final height was –1.7 ± 1.3 SDS, being 162.9 ± 7.2 cm in the boys and 149.8 ± 6.7 cm in the girls. Studies on final height in GHD reported in the literature during the last 5 years show mean final height results between –3.0 and –0.7 SDS [6, 7, 8, 9, 20, 21, 22, 23, 24, 25, 26]. In most of these studies patients were treated with different treatment regimens going from low doses of rhGH administered 3 times a week to daily high doses of rhGH adapted as a function of body weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 34 GHD patients, of whom 6 had isolated GHD and 28 multiple pituitary hormonal deficiencies, treated with 2 or 3 weekly injections of extracted hGH, final height was –1.7 ± 1.3 SDS, being 162.9 ± 7.2 cm in the boys and 149.8 ± 6.7 cm in the girls. Studies on final height in GHD reported in the literature during the last 5 years show mean final height results between –3.0 and –0.7 SDS [6, 7, 8, 9, 20, 21, 22, 23, 24, 25, 26]. In most of these studies patients were treated with different treatment regimens going from low doses of rhGH administered 3 times a week to daily high doses of rhGH adapted as a function of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Brämswig et al [6]treated 36 GHD patients, of whom 28 had idiopathic GHD, with subcutaneous rhGH 6–7 times/week in a dose of 13.7 ± 1.1 IU/m 2 /week (equivalent to 0.5 IU/kg/week) and found a mean final height of –1.1 ± 0.9 SDS (compared to Swiss growth references [27]). Blethen et al [7]reported a final height SDS of –0.7 ± 1.4 SDS (compared to American growth references [28]) in 121 GHD patients (102 idiopathic GHD) treated randomly with daily or three times a week rhGH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these improvements in therapy, however, published results in terms of AH continue to be unsatisfactory (table 1); in these studies, GHD of different aetiologies (idiopathic and organic) were analyzed together, the age at start of treatment was variable [10], and some patients did not receive daily therapy [10, 11, 12]. These factors might have contributed to the controversial results obtained [10].…”
Section: Adult Height Of Growth Hormone Deficient Patientsmentioning
confidence: 99%
“…In many studies, however, the age at the start of treatment ranged from 8.4 to 12.9 years [10, 12, 13, 14, 15, 16, 17], suggesting the possibility of a delay in the diagnosis. This delay could also explain, at least in part, the suboptimal therapeutic results (table 3).…”
Section: Influence Of Early Gh Treatment On Ah In Patients With Idiopmentioning
confidence: 99%